2020
DOI: 10.3390/ani10071181
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Luteum Color Doppler Ultrasound and Pregnancy Outcome in Buffalo during the Transitional Period

Abstract: This study evaluated corpus luteum (CL) development in buffaloes out of breeding season and assessed an early pregnancy diagnosis. Mediterranean buffaloes (n = 29) were synchronized and artificially inseminated. CL B-mode/color Doppler ultrasonography examinations were performed daily from Days 5 to 10 post-synchronization, recording CL dimensions and blood flow parameters. Blood samples were collected on the same days for the progesterone (P4) assay. Data were grouped into pregnant or nonpregnant and retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
1
6
0
2
Order By: Relevance
“…The placenta's size is critical for supporting appropriate fetal growth. The weight of the placenta in the normal pregnancy group was substantially higher than that in the HDCP group, according to Esposito et al [ 31 ]. The severe group had significantly lower weeks of delivery, placental weight, and neonatal birth weight than the normal and mild groups, which was consistent with the previous study.…”
Section: Resultsmentioning
confidence: 93%
“…The placenta's size is critical for supporting appropriate fetal growth. The weight of the placenta in the normal pregnancy group was substantially higher than that in the HDCP group, according to Esposito et al [ 31 ]. The severe group had significantly lower weeks of delivery, placental weight, and neonatal birth weight than the normal and mild groups, which was consistent with the previous study.…”
Section: Resultsmentioning
confidence: 93%
“…Monteiro et al [ 36 ] also demonstrated a high correlation between the size of the dominant follicle at TAI and both ovulation and pregnancy rate at 45 days post-AI. Furthermore, larger follicles were also associated with larger corpora lutea and augmented progesterone secretion [ 22 ], reducing the incidence of embryonic mortality [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the day of AI, the animals underwent ultrasound examination (MyLab 30Gold ® ; Esaote, Genova, Italy), and the size of the preovulatory follicle was recorded. The area of the preovulatory follicle was calculated as previously described [ 22 ]: where: FL = follicle a = major axis of the follicle b = minor axis of the follicle …”
Section: Methodsmentioning
confidence: 99%
“…Para responder a una demanda actual creciente de leche y carne, la ganadería bovina tiene que aumentar su oferta, y por eso debe optimizar sus rendimientos al máximo (Esposito, Salzano, Russo, de Nicola, Prandi, Gasparrini, Campanile y Neglia, 2020). A la hora de intensificar la producción, uno de los objetivos es lograr un intervalo entre partos (IPP) mínimo y, un número de terneros viables comercializables máximo (Reese, Franco, Poole, Hood, Fernadez Montero, Oliveira Filho, Cooke y Pohler, 2020).…”
Section: Introductionunclassified